2007
DOI: 10.1136/qshc.2006.021014
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety: helping medical students understand error in healthcare

Abstract: Objective: To change the culture of healthcare organisations and improve patient safety, new professionals need to be taught about adverse events and how to trap and mitigate against errors. A literature review did not reveal any patient safety courses in the core undergraduate medical curriculum. Therefore a new module was designed and piloted. Design: A 5-h evidence-based module on understanding error in healthcare was designed with a preliminary evaluation using self-report questionnaires. Setting: A UK med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
113
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 23 publications
8
113
0
6
Order By: Relevance
“…Reported studies, however, have identified deficiencies in patient safety training, and an explicit curriculum on patient safety is only available at a limited number of medical schools (Fulton 2004;Madigosky et al 2006;Patey et al 2007;Newell et al 2008;Alper et al 2009;Flin et al 2009). The implementation of patient safety teaching can be challenging.…”
Section: Patient Safety For Medical Studentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reported studies, however, have identified deficiencies in patient safety training, and an explicit curriculum on patient safety is only available at a limited number of medical schools (Fulton 2004;Madigosky et al 2006;Patey et al 2007;Newell et al 2008;Alper et al 2009;Flin et al 2009). The implementation of patient safety teaching can be challenging.…”
Section: Patient Safety For Medical Studentsmentioning
confidence: 99%
“…Our brief programs have failed to promote a healthy reporting culture amongst our students, and they continued to rate their knowledge in patient safety as 'fair' or 'poor' only. These are important areas for improvement and it is likely that a more comprehensive and longitudinal program is needed (Fischer et al 2006;Patey et al 2007;Pearson et al 2010). We have since introduced patient safety in other clinical years in order to ensure the maintenance of new knowledge.…”
Section: Patient Safety For Medical Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some attempts have been made to evaluate patient safety education. For example, Patey et al (2007) evaluated the development of a new patient safety module for medical students in the UK and, although the attitude measure they used to evaluate the success of the new module was theoretically derived, it was not validated. Muller and Ornstein (2007) also measured attitudes of medical trainees, including medical students, this time focussing on the perceived consequences of making a medical error with more or less serious outcomes.…”
Section: Practice Pointsmentioning
confidence: 99%